IMPLEMENTATION OF THE NAÏVE BAYES ALGORITHM IN THE DESIGN OF INFORMATION SYSTEMS FOR THE DEVELOPMENT OF STUDENT ACADEMIC ACHIEVEMENT - Hartatik Hartatik; Elvina Yuliani (International Journal of Multidisciplinary Research and Literature, 2022)
The research conducted in this journal is the design of an information system on the development of student achievement using the Naive Bayes algorithm. The purpose of research and development of this system is to help students find predictions of early graduation and allow the admin to find out progress and forecasts of active student graduation. This research begins with the design of the business process of the actor who will see the prediction of graduation. In designing the application, FR tables, use case diagrams, use case scenarios, class diagrams, and sequence diagrams are created. Then proceed with database design in the form of Entity Relationship Diagram (ERD), Relationship Between Tables (RAT) and table design. After designing the database, a user interface design is made in the form of a mockup. The result of the research in this final project is creating a Student Achievement design of Development Information System with the Naive Bayes Algorithm. This information system comes from application design, database design, user interface design, and system testing design which is then implemented to calculate graduation predictions based on student academic achievement.